The role of s-palmitoylation in neurological diseases: implication for zDHHC family - Liao, Dan; Huang, Yutao; Liu, Dan; Zhang, Haofuzi; Shi, Xinyu; Li, Xin; Luo, Peng (Frontiers in Pharmacology, 2024)
S-palmitoylation is a reversible posttranslational modification, and the palmitoylation reaction in human-derived cells is mediated by the zDHHC family, which is composed of S-acyltransferase enzymes that possess the DHHC (Asp-His-His-Cys) structural domain. zDHHC proteins form an autoacylation intermediate, which then attaches the fatty acid to cysteine a residue in the target protein. zDHHC proteins sublocalize in different neuronal structures and exert dif-ferential effects on neurons. In humans, many zDHHC proteins are closely related to human neu-rological disor-ders. This review focuses on a variety of neurological disorders, such as AD (Alz-heimer's disease), HD (Huntington's disease), SCZ (schizophrenia), XLID (X-linked intellectual disability), ADHD (attention deficit hyperactivity disorder) and glioma. In this paper, we will discuss and summarize the research progress regarding the role of zDHHC proteins in these neu-rological disorders.